PDL1-binding peptide/anti-miRNA21 conjugate as a therapeutic modality for PD-L1high tumors and TAMs - Kim, Eun Hye; Lee, Jongwon; Kwak, Gijung; Jang, Hochung; Kim, Hyosuk; Cho, Haeun; Jang, Yeongji; Choi, Jiwoong; Chi, Sung Gil; Kim, Kwangmeyung; Kwon, Ick Chan; Yang, Yoosoo; et al. (Elsevier BV, 2022)
Upregulation of oncogenic miRNA21 (miR-21) plays a pivotal role in proliferation, migration and invasion of cancer cells. In addition to cancer cells, tumor-associated macrophages (TAMs) also have high abundance of miR21, which accelerates malignant progression of tumors in the late stages of carcinogenesis. Despite of the protumorigenic functions of miR-21 in TAMs and cancer cells, reliable therapeutic strategies to simultaneously inhibit miR-21 activity in both types of cell have not yet been developed. In this study, we designed a dualtargeting drug delivery system of miR-21 inhibitors that could bind to both tumor cells and macrophages with overexpressed PD-L1 receptors. This peptide-oligonucleotide conjugate (Pep-21) consists of a PDL1-binding peptide covalently linked with an anti-miR-21 inhibitor via click chemistry. Pep-21 was preferentially internalized in both cell types, consequently depleting endogenous miR-21. Our studies found that Pep-21 treatment reduced tumor cell migration, reprogrammed immunosuppressive M2-type TAMs into M1-type macrophages, and restrained tumor progression. Collectively, neutralization of miR-21 activity in both cancer cells and TAMs can be a promising strategy for effective antitumor responses.